Gender Differentials and Agricultural Productivity in Niger - Backiny-Yetna, Prospere; McGee, Kevin (World Bank Group, Washington, DC, 2015)
Most of the poor in Sub-Saharan Africa live in rural areas where agriculture is the main income source. This agriculture is characterized by low performance and its productivity growth has been identified as a key driver of poverty reduction. In Niger, as in many other African countries, productivity is even lower among female peasants. To build policy interventions to improve agricultural productivity among women, it is important to measure the potential gap between men and women and understand the determinants that explain the gap. This paper uses the Oaxaca-Blinder decomposition methodology at the aggregate and detailed levels to identify the factors that explain the productivity gap. The analysis finds that in Niger on average plots managed by women produce 19 percent less per hectare than plots managed by men. It also finds that the gender gap tends to be widest among Niger's most productive farmers. The primary factors that contribute to the gender productivity gap in Niger are: (i) farm labor, with women facing significant challenges in accessing, using, and supervising male farm labor; (ii) the quantity and quality of fertilizer use, with men using more inorganic fertilizer per hectare than women; and (iii) land ownership and characteristics, with men owning more land and enjoying higher returns to ownership than women.